Climate change and coastal ecosystems long-term effects of climate and nutrient loading on trophic organization - Livingston, Robert J. (Marine science series, 2015)
"Based upon a four decade longitudinal study of river-estuarine systems in the Northeast Gulf of Mexico, this book provides a detailed comparative analysis of the long-term data with specific references to similarities and differences in system response to nutrient loading (natural and anthropogenic) and long-term climatological cycles. It includes specific references to noted changes in the climate of the study regions over the four decades of field operations. The unique database will allow a totally new approach to the differentiation of anthropogenic processes relative to natural conditions in a series of river-estuarine systems."--Provided by publisher